Implementasi Pembelajaran Tahfiz Al-Qur’an Juz 30 dengan Metode Jama’ dan Talaqqi - Tahiyah; Dewi Maharani (STIT Muslim Asia Afrika, 2022)
The application of learning to memorize Al-Qur`ān Juz 30 at TPQ At-Thohiriyyah uses jama' method and talaqqi method, is students read the Qur`ān simultaneously and are guided by the teacher, then students go forward in turn reading their memorization and the teacher corrects it directly . The purpose of the study was to determine the implementation of the jama' and talaqqi methods in learning taḥfiẓ Al-Qur`ān juz 30 at TPQ At-Thohiriyyah Songgom Brebes. This research uses descriptive qualitative research. The main data sources are the Head of Madrasah, Teacher Taḥfiẓ, and third grade students at TPQ At-Thohiriyyah Songgom Brebes. Data collection techniques used are observation, interviews and documentation. The findings in this study indicate that in the implementation of learning taḥfiẓ Al-Qur`ān juz 30 at TPQ At-Thohiriyyah using the jama' method and the talaqqi method in its implementation is less successful. The number of student achievements is still small in memorizing chapter 30 within 3 years, so that students have low reading and memorization skills and the majority of students' ages are relatively early.